1993
DOI: 10.1002/arch.940240204
|View full text |Cite
|
Sign up to set email alerts
|

Postendocytic vitellin processing in ovarian follicles of the stick insect Carausius morosus (Br.)

Abstract: Newly laid eggs of the stick insect Carausius morosus contain two native vitellins (Vit A and Vit 6). Under denaturing conditions, these vitellins resolved into 3 (AI, A2, and A3) and 2 (61 and B2) polypeptides. All of these polypeptides had counterparts in the female hemolymph from which they were shown to be derived by in vivo labelling. During ovarian development, the 2 vitellins changed both in charge and polypeptide composition. In EV and LV follicles, Vit A resolved into 4 distinct vitellin polypeptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The decrease in the content of glucose of VT3 must be attributed to the post-endocytic processing of VG. Post-endocytic processing of VT has already been reported by Giorgi et al (1993). The lack of glucose in the oligossacharide associated with VT2 can be attributed to its different origin.…”
Section: Vitellins and Vitellogeninsmentioning
confidence: 68%
“…The decrease in the content of glucose of VT3 must be attributed to the post-endocytic processing of VG. Post-endocytic processing of VT has already been reported by Giorgi et al (1993). The lack of glucose in the oligossacharide associated with VT2 can be attributed to its different origin.…”
Section: Vitellins and Vitellogeninsmentioning
confidence: 68%
“…The enzymes include b-N-acetylglucosaminidase in Xenopus (Wall and Meleka, 1985), and serine proteases and cathepsin B and L in Drosophila and Bombyx Medina et al, 1988;Medina and Vallejo, 1989). Giorgi et al (1993b) have suggested that Golgi-derived vesicles deliver hydrolytic enzymes from the Golgi complex to the yolk bodies.…”
Section: General Characteristics Of Receptormediated Endocytosismentioning
confidence: 99%
“…Yolk is transferred to the ovarian follicle by a process of endocytosis from the maternal bloodstream (27). Yolk precursors or vitellogenins are high molecular weight lipo-glycoproteins (16) synthesized in the female fat body (26), and extensively modified prior to secretion into the haemolymph (1 8, 19) and endocytosis by the oocyte (9,30). Once in the oocyte, vitellins are partitioned in the yolk granules for long term storage (24).…”
Section: Introductionmentioning
confidence: 99%